Effect of Tea (Camellia sinensis L.) on Lipid Peroxidation in Rat Liver and Kidney : a Comparison of Green and Black Tea Feeding - SANO, Mitsuaki; OGUNI, Itaro; YOSHINO, Kyoji; KONOMOTO, Haruo; NAKAMURA, Yoshiyuki; TAKAHASHI, Yutaka; TOMITA, Isao; SHIMOI, Kayoko (Biological & pharmaceutical bulletin, 1995)
The antioxidant effects in the liver and kidney obtained from rats fed diets containing 3% green or black tea leaf powder, which were prepared from the same lot tea leaves, were studied using the tissue slice-antioxidant evaluation method with two lipid peroxidation inducers. After 50 d on the diets, liver slices prepared from green and black tea-supplemented rats showed significant inhibitory effects against tert-butyl hydroperoxide-induced lipid peroxidation. These effects, however, were not proportional to the amounts of (-)-epicatechins and antioxidant vitamins in the tea leaves. In the kidney, the antioxidant effect was observed only in the green tea-fed group. A similar antioxidant effect on the kidney was observed after oral administration of a major tea polyphenol, (-)-epigallocatechin gallate (50 mg/kg body weight for. 7d). Liver slices from black tea-fed rats also inhibited bromotrichloromethane-induced lipid peroxidation. These results demonstrated that dietary green and black tea had antioxidant effects on tissue lipid peroxidation ex vivo.